Digitalization of Islamic Religious Education Learning in the Era of the Industrial Revolution 5.0: A Theoretical Analysis of Innovation, Challenges, and Islamic Values - Ainur Rofiq Sofa; Ummi Jamilatul Qamariyah (Abjadia : International Journal of Education, 2026)
The digital transformation driven by the Industrial Revolution 5.0 has profoundly influenced educational practices, including Islamic Religious Education (IRE). This shift demands that Islamic education not only integrate digital technologies in an adaptive manner but also ensure that their application remains consistent with Islamic humanistic and spiritual principles. This article seeks to theoretically explore the digitalization of IRE learning in the context of the Industrial Revolution 5.0 by examining various forms of digital-based instructional innovation as well as the ethical and value-based challenges associated with their implementation. The study adopts a qualitative descriptive design through library research, analyzing 11 peer-reviewed journal articles published between 2020 and 2025 that address the digital transformation of Islamic education. Content analysis is employed to extract key concepts, empirical findings, and relevant theoretical perspectives related to digital IRE learning. The results demonstrate that the use of digital technologies such as Learning Management Systems (LMS), digital Qur’an applications, and artificial intelligence based learning tools has a positive impact on student engagement, learning flexibility, and access to diverse Islamic knowledge resources. Nevertheless, the digitalization of IRE learning also encounters several challenges, including insufficient digital literacy among educators, the risk of moral erosion within digital environments, and disparities in educational infrastructure. Consequently, the development of digital-based IRE learning should be firmly anchored in the principles of maqāṣid al-syarī‘ah, ensuring that technological advancement serves not only functional efficiency but also moral formation, spiritual strengthening, and the promotion of public welfare. These findings provide a conceptual framework for the digitalization of Islamic Religious Education that is human-centered and grounded in Islamic values.